Level of Participants Satisfaction With Implementastion The PORSENASMA IV Of Badminton 2022 - Pramudya Widhyanto; Irwan Setiawan; Moh. Nurkholis (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
The purpose of this study is to find out the level of satisfaction of participants with the implementation of Porsenasma IV 2022 in badminton sports and the results of this study can later be used as a model for organizing a sports festival event. This type of research is descriptive quantitative, sampling technique using incidental sampling technique, as many as 30 respondents. Data analysis techniques use percentages. The results of manual calculations based on the dimensions of quality are for the dimension of direct evidence (tangibles) which is equal to 80%, which means it is in the category of satisfying criteria, the dimension of empathy (empathy) is equal to 84% which means it is in the category of very satisfying criteria, the dimension of reliability (reliability) is 84% which means it is in the very satisfying category, the responsiveness dimension is 78% which means it has satisfying criteria, the certainty dimension (assurance) is 82% which means it is in the very satisfying criteria category. For the dimensions of the largest participant satisfaction level, the dimensions of empathy (empathy) and reliability dimensions are 84%, while the level of contingent satisfaction with the implementation of the 2022 Porsenasma IV badminton sports branch is very satisfying, because seeing the filling out of a questionnaire by respondents from participants of the 2022 Porsenasma IV branch badminton sport is very fulfilling and fulfilling. So that the average percentage of all question items is 81.6%, which means they are in the very satisfying category